Diversidade dos Cyclopoida (Copepoda, Crustácea) de água doce do estado de São Paulo: taxonomia, ecologia e genética - Silva, William Marcos da (2003)
In the present work, the diversity of the Copepoda Cyclopoida from Sao Paulo State was studied. Samples of zooplankton were collected along with water samples were collected in 22 Hydrographic Management Units (UHGRH) of the State. Different environments, such as Reservoirs, Ponds, and Rivers were sampled totalizing 207 water bodies. All of them were positioned by using GPS. Samples of zooplankton were collected using net with 68µm of mesh size. Vertical hauls were performed in limnetic zone, while in littoral zone horizontal hauls and bucket were used. The plankton samples were preserved in formaldehyde 4%. Identifications of Cyclopoida were achieved using adult females forms. The data thus obtained were submitted to the SinBiota World Web Site where Geographical distribution of Cyclopoida was plotted to the map of the Sao Paulo State using the geographic coordinates obtained from GPS. It was compared the biodiversity and abundance of Cyclopoida in Reservoirs with different trophic degrees located in the Basins of rivers Tietê, Ribeira do Iguape, and Grande. ITS 2 sequence of DNA of the Cyclopoida was obtained for the following species: Thermcyclops decipiens, Thermocyclops inversus, Mesocyclops ogunnus and Mesocyclops longisetus longisetus. Number of chromosomes Mesocyclops longisetus longisetus was counted and a chromatin diminution observed. New Cyclopoida species, Thermocyclops n. sp., was first described and five species, Acanthocyclops robustus, Eucyclops elegans, Eucyclops cf. prinophorus, Microcyclops alius, and Mesocyclops aspericornis, were newly registered in the São Paulo State. With this, there are now 10 genera and 26 species recorded in the Sao Paulo State. A key to genres and species in the São Paulo State was proposed based on morphological differences, including draws from the anatomical characteristics which are important for taxonomy. It was proved that species identified earlier in the São Paulo State as Mesocyclops kieferi and Mesocyclops brasilianus were actually confused with species Mesocyclops ogunnus and Mesocyclops meridianus, respectively. It was found that Pacyclops fimbriatus, recorded earlier in the Broa Reservoir, is actually Pacyclops chiltoni inhabiting Sao Paulo water bodies. Thermocyclops decipiens was found to be the most broadly distributed species of the Cyclopoid recorded in 20 of 22 hydrographic units followed by Mesocyclops longisetus longisetus recorded in 16 units and Thermocyclops mintus, Mesocyclops ogunnus and Mesocyclops meridianus recorded in 15 units. Based on our observations, we concluded that, in contrast to the common opinion, highly eutrophicated Reservoirs present the highest species richness and distribution equitability as compared to oligotrophic ones. It was found that Acanthocyclops robustus, Mesocyclops ogunnus, and Thermocyclops inversus present the high abundance in eutrophic systems, along with Thermocyclops decipiens. On the other hand, Thermocyclops n. sp., as well as Thermocyclops minutus, have presented the high abundance in systems less eutrophicated streams. We found that the newly described species Thermocyclops n. sp is distributed specifically in the Basins of Ribeira do Iguape and Paraíba do Sul. ITS 2 sequence of DNA varied greatly between different species, while no significantly variation was observed between specimens of the same species. Mesocyclops longisetus longisetus was found to possess 2n = 14 chromosomes and presented the chromatin diminution in 4th egg cleavage. The present study clearly shows that the exhaustive study of the biodiversity needs the use complex approaches as taxonomy, ecology and genetics. This work is part of Biota/FAPESP program, the virtual institute of biodiversity.